Analisis Beban Kerja dan Kebutuhan Petugas Unit Rekam Medis di RSUP Dr. Sitanala - Nabila Zahara Ramadan; Puteri Fannya; Deasy Rosmala Dewi; Daniel Happy Putra (Pusat Riset dan Inovasi Nasional, 2025)
Hospitals, as healthcare service providers, are required to improve the quality and efficiency of their services, one of which is through the implementation of Electronic Medical Records (EMR). This transformation impacts the workload of staff, particularly in the Medical Records Unit. This study aims to analyze the workload and staffing needs of the Medical Records Unit at Dr. Sitanala Central General Hospital using a descriptive quantitative approach with the Health Workload Analysis (ABK-Kes) method. Data were collected through observation and interviews with six staff members using observation sheets, interview guidelines, and informed consent forms. The results show that the Available Working Time (AWT) is 72,000 minutes per year, exceeding the national standard. There are 11 core tasks and 3 supporting tasks, with the highest Standard Workload (SWL) found in the recording and filing activity (72,000), and the Standard Supporting Task (SST) value is 1.2. Based on achievements, SWL, and SST, a total of four staff members are needed to balance the workload. Currently, only one staff member remains due to staff rotation, resulting in a shortage of three personnel. Therefore, Dr. Sitanala Hospital needs to recruit three additional medical record officers with a minimum qualification of a D3 in Medical Records to maintain optimal service and manageable workloads.